Fungsi Azan dalam Kehidupan Keagamaan Menurut Buya Hamka: Analsis Tafsir Historis - Vina Amelia; Salahuddin Harahap (Kartika: Jurnal Studi Keislaman, 2026)
The practice of adhan outside the context of obligatory prayers (non-salat adhan) often sparks epistemological debates between the formalism of Islamic law (sharia) and local tradition (culture). This study aims to reconstruct the concept of the adhan's function in religious life through the integration of tafsir methodology and phenomenological approaches. Primary data are sourced from Tafsir Al-Azhar by Buya Hamka, supported by other exegetical literature and classical-modern jurisprudence, as well as field data on the traditions of adhan for disaster aversion and adhan for the deceased in graves. Textual analysis employs Abdul Mustaqim's framework of tafsir reconstruction, then dialectically analyzed using Max van Manen's Phenomenology of Practice to capture the lived experiences of the practicing community. The findings reveal that the transformation of non-salat adhan functions in public spaces is fragmented into four continuous typological dimensions: the educational-monotheistic dimension at birth, the protective-situational dimension during natural disasters (al-hariq), the eschatological-therapeutic dimension in funeral ceremonies, and the psychological-therapeutic dimension to alleviate existential anxiety (al-mahzun). The study concludes that for the community's spiritual consciousness, sharia is not experienced rigidly but is humanistically fused as a transcendental instrument that continuously preserves the soul's connection to monotheistic values from the cradle to the grave. This research offers a new contribution in mapping the therapeutic and sociological functions of religious audio symbols in public spaces.